A Multicoefficient Slip-Corrected Reynolds Equation for Micro-Thin Film Gas Lubrication - Eddie Yin-Kwee Ng; Ningyu Liu (International Journal of Rotating Machinery)
This work investigates and analyzes the performance of conventional slip models among various regimes of Knudsen number and developes a new multicoefficient slip-velocity model, by using Taguchi quality control techniques and numerical analysis. A modified Reynolds equation is also derived based on the new slip-flow model. The multicoefficient slip model and its slip-corrected Reynolds equation are suitable to a wide Knudsen range from slip to transition regime. In comparison with other conventional slip models, it is found that the current results have a better agreement with the solution obtained from the linearized Boltzmann equation and direct simulation of Monte Carlo method (DSMC).